Heaps’ Law and Heaps functions in tagged texts: evidences of their linguistic relevance - Chacoma, A. (2020)
Fil: Zanette, Damian Horacio Comisión Nacional de Energía Atómica. Instituto Balseiro; Universidad Nacional de Cuyo, Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas, Argentina